Co-creation and Evaluation of an Adapted Physical Activity Toolkit: Guidelines To Support Practice Among Rehabilitation Professionals in Community Organizations - Annabelle de Serres-Lafontaine; Roxanne Périnet-Lacroix; Charles Sebiyo Batcho; Krista L. Best (Physical Activity and Health, 2023)
Background: Limited knowledge and skills of health professionals is a common barrier when adapting physical activity for people with disabilities. A community organization (Adaptavie) identified the need for improved training and resources to facilitate APA prescription by their employees. The objectives of this research were to co-create an APA toolkit and evaluate implementation. Methods: A multi-method participatory research approach was used with kinesiologists who worked at Adaptavie. The project consisted of two phases: P1) co-creation of the toolkit; P2) implementation evaluation. Sociodemographic information (P1; P2), the Work self-efficacy Inventory Survey (P1; P2), the Indicators of Success Questionnaire (P2) and focus groups (P1 n = 3; P2 n = 1) were conducted with kinesiologists. Summary statistics were described (sociodemographic and questionnaires) and analysed thematically (focus groups). Results: The co-creation of an evidence-based training toolkit contained information about 45 types of disabilities. Five to eight kinesiologists (depending on the phase) reported improvements in workplace self-efficacy, skills and knowledge after using the APA toolkit for one year. Following implementation, the APA toolkit was reported to have a high level of usability and fidelity. Conclusion: A co-created APA toolkit supported kinesiologists to prescribe evidence-based APA programs by increasing their knowledge, skills and self-efficacy.